2012
DOI: 10.1140/epje/i2012-12060-7
|View full text |Cite
|
Sign up to set email alerts
|

Shear-affected depletion interaction

Abstract: Abstract.We investigate the influence of flow fields on the strength of the depletion interaction caused by disc-shaped depletants. At low mass concentration of discs, it is possible to continuously decrease the depth of the depletion potential by increasing the applied shear rate until the depletion force is not perceivable experimentally. Above a threshold in the platelet mass concentration, the depletion potential can no longer be affected by flow in the accessible range of shear rates. While the observed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Sphere/wall and sphere/sphere interactions in a dilute suspension of infinitely thin rods were numerically calculated [13]. Shear-affected depletion interactions with disc-shaped particles were experimentally studied [14]. A detailed review on depletion surface forces can be found in the book by Lekkerkerker and Tuinier [15].…”
Section: Introductionmentioning
confidence: 99%
“…Sphere/wall and sphere/sphere interactions in a dilute suspension of infinitely thin rods were numerically calculated [13]. Shear-affected depletion interactions with disc-shaped particles were experimentally studied [14]. A detailed review on depletion surface forces can be found in the book by Lekkerkerker and Tuinier [15].…”
Section: Introductionmentioning
confidence: 99%
“…Theories have also addressed the case of active colloids immersed in a bath of passive depletants [ 65 ], nanobubbles [ 66 ], nanoparticles [ 67 , 68 , 69 , 70 , 71 ], microgels [ 72 ], and bacterial systems [ 73 ]. One should also mention the theoretical efforts intended to characterize the depletion phenomena in confined domains [ 74 , 75 ], as well as near dielectric discontinuities [ 76 ] and in shear conditions [ 77 ]. For a review of the research about the topic in both bulk and confined domains see for instance Trokhymchuk et al [ 74 ].…”
Section: Introductionmentioning
confidence: 99%